Alirocumab and chest pain after acute coronary syndrome: An analysis of ODYSSEY OUTCOMES - Gregory P. Geba; Ruifeng Chen; Kasturi Talapatra; Taylor Brackin; Kusha A. Mohammadi; Robert Pordy; Garen Manvelian; David J. Maron; Gregory G. Schwartz; Michael Szarek; Ph. Gabriel Steg; Sergio Fazio (American Journal of Preventive Cardiology, 2024)
Background: Patients with recent acute coronary syndrome (ACS) commonly experience chest pain, which affects quality of life even when not due to recurrence of ACS. This post hoc analysis of ODYSSEY OUTCOMES assessed the effect of alirocumab, a proprotein convertase subtilisin/kexin type 9 inhibitor, on the incidence of chest pain not due to recurrent ACS. Methods: Patients with recent ACS (n = 18,894) and elevated atherogenic lipoprotein levels despite optimized statin therapy were randomized to subcutaneous alirocumab or matching placebo every 2 weeks. Alirocumab dose was adjusted to target low-density lipoprotein cholesterol (LDL-C) 25–50 mg/dL (0.6–1.3 mmol/L) and to avoid consecutive LDL-C <15 mg/dL (0.39 mmol/L). Non-hospitalized chest pain adverse events and chest pain events requiring hospitalization but negatively adjudicated for recurrent ACS were assessed. Results: Chest pain not requiring hospitalization was reported as an adverse event in 1490 patients, including 7.5 % and 8.3 % of alirocumab and placebo groups, respectively. Hospitalization for chest pain negatively adjudicated for recurrent ACS occurred in 952 patients, including 4.8 % and 5.3 % of alirocumab and placebo groups, respectively. Adjusting for baseline covariates, alirocumab use was associated with 8.1 % lower risk of chest pain (either non-hospitalized or hospitalized events) versus placebo (HR: 0.919; 95 % CI: 0.845–0.998; P = 0.046); a landmark analysis at 7 months showed a larger, 11.7 % risk reduction (HR: 0.883; 95 % CI: 0.793–0.984; P = 0.024). Conclusions: Alirocumab use is associated with reduced incidence of chest pain events after ACS, including those not requiring hospitalization and those requiring hospitalization but not adjudicated as recurrent ACS. Trial registration: NCT01663402